Perspectivas do espelho: o duplo em Dostoiévski, Fuentes e Hugo Mãe - Andreatta, Lucas Ricardo (2021)
This dissertation presents an analysis of three novels: The Double (2014), by Fyodor Dostoyevsky, Aura (2015), by Carlos Fuentes, and The dehumanization (2014), by Valter Hugo Mãe. The aim of this work is to discuss the double phenomena in those books, relating it to the self’s configuration meaning in the Modern Age. Also, we consider contexts in which those novels occur. In those countries, the Modern Age occurs fragmentally. As a result, it did not bring a state of social welfare to the people. In this sense, we intend to observe how those different authors, in their different contexts, characterizes the double in countries where one had to face historical multitemporalities, according to the concept of Néstor García Canclini (2013). For that, we take into consideration the double concepts of Otto Rank (2014) and Sigmund Freud (1996) as well as Remo Ceserani (2006), Rosemary Jackson (2009), and Clément Rosset (2008), respectively related to psychoanalysis, fantastic literature, and contemporary philosophy. Furthermore, we use the concept of identity of Stuart Hall (2011) to observe how the double is related to it in modernity. Our objects are analyzed according to Fábio Durão’s assumptions, to whom the exercise of interpretation requires a critical perspective, further than a scientific view. With this research, we aim to reinterpret those works and promote new studies, as well as to comprehend those times and spaces.